Ethics of war and peace in Iran and Shiʻi Islam - Mahallati, Mohammad Jafar Amir, 1952- (Toronto : University of Toronto Press, 2016)
"Nearly four decades after a revolution, experiencing one of the longest wars in contemporary history, facing political and ideological threats by regional radicals such as ISIS and the Taliban, and having succeeded in negotiations with six world powers over her nuclear program, Iran appears as an experienced Muslim country seeking to build bridges with its Sunni neighbours as well as with the West. "Ethics of War and Peace in Iran and Shi'i Islam explores the wide spectrum of theoretical approaches and practical attitudes concerning the justifications, causes and conduct of war in Iranian-Shi'i culture. By examining primary and secondary sources, and investigating longer lasting factors and questions over circumstantial ones, Mohammad Jafar Amir Mahallati seeks to understand modern Iranian responses to war and peace. His work is the first in its field to look into the ethics of war and peace in Iran and Shi'i Islam. It provides a prism through which the binary source of the Iranian national and religious identity informs Iranian responses to modernity. By doing so, the author reveals that a civilization-conscious soul in modern Iran is re-emerging"--Provided by the publisher
Preface and acknowledgments. Introduction. Part 1 The ethics of war and peace in Iran: epic literature, philosophy, theology, and chivalry : The ethics of war and peace in epic Persian literature: Shahnameh of Ferdowsi -- Iranian classical thinkers on war and peace: a select view -- War and chivalry in the annals of Iranian history and ethical imagination -- Modern Iranian intellectuals on the ethics of enmity and nonviolence. Part 2 The Jihad jurisprudence: its developments and critics in Iran : War and peace in Shiʻi primary narratives and sources -- Traditional Shiʻi ethics of war and peace untested: Jihad, ideology, revolution, and war -- Postwar revision and the reconstruction of modern Iranian Shiʻi ethics of war and peace -- Terrorism and Shiʻi theologies of martyrdom, nonviolence, and forgiveness -- Diplomacy in between nuclear technology and antibomb theology. Conclusion: beyond a minority mentality: the emerging Shiʻi-Iranian cosmopolitanism. Appendix 1: "Jihad:" a historical overview of the concept and its politics (English translation of an article published in the "Great Islamic Encyclopedia," first edition, Iran) -- Appendix 2: "Jang" (war; Persian): laws in war according to Twelver-Shiʻi jurisprudence (English translation of an article published in the "Great Islamic Encyclopedia," first edition, Iran) -- Appendix 3: Iran's official position on war crimes by Daesh -- Appendix 4: advice and guiding to the fighters on the battlefields: a Shiʻi manual.
Includes bibliographical references (pages 317-333) and index.
Online resource; title from digital title page (EbscoHost platform, viewed April 5, 2017).
JSTOR
Keywords: Peace -- Moral and ethical aspects -- Iran; War -- Moral and ethical aspects -- Iran; War -- Religious aspects -- Islam; Peace -- Religious aspects -- Islam; Shīʻah -- Iran; Shiites -- Iran; Jihad; Paix -- Aspect moral -- Iran; Guerre -- Aspect moral -- Iran; Guerre -- Aspect religieux -- Islam; Chiisme -- Iran; Chiites -- Iran; Jihād.; RELIGION -- Islam -- General; RELIGION -- Religion, Politics & State; War -- Religious aspects -- Islam; War -- Moral and ethical aspects; Jihad; Peace -- Moral and ethical aspects; Peace -- Religious aspects -- Islam; Shīʻah; Shiites; Iran